New design method of unequal taper thread (UTT) pairs and its application in API NC38 thread improvement - Hangming Liu; Yangye He; Jifang Wan; Lin Chen; Xianzhong Yi; Song Hou; Yanbin Wang; Dongxu He; Gang Li (Petroleum, 2023)
API standard threads are the most commonly used thread configurations for drill pipe joints in the petroleum industry. Recently with the increasing application of horizontal wells and extended-reach wells in drilling engineering, drill pipe joint threads are subjected to complex loads, and drill pipe joint thread breakage accidents occur frequently. The API NC38 threaded pair used in the SU36-8-4H2 well suffered a fracture accident. Macroscopic analysis found that the fracture sites were located near the root of the first engagement pin-thread where the stress was greatest. Therefore, it is necessary to find an alternative method to reduce the largest stress of NC38 threads. Then, a new design method of unequal taper thread (UTT) pairs is proposed that the taper of pin thread, slightly smaller than the taper of matched-box thread, is not equal to one of box-thread. In the UTT pairs of API NC38 thread, the taper of box thread is kept as the standard taper of 1:6, but the taper of pin thread is, respectively, 1:6.1 (UTT-I), 1:6.2 (UTT-II), 1:6.3 (UTT-III) and 1:6.4 (UTT- IV). The 3D finite element models of four UTT pairs and one standard pair based on NC38 thread were developed, and the mechanical properties of five thread pairs bearing such typical working loads as torque, axial compression, axial tension, bending moment, internal and external pressure, were analyzed. The results show that four UTT pairs are superior to the standard pair of API NC38, and UTT-III has the most performance in all of four UTT pairs. Compared with the standard pair of API NC38, UTT-III pair can improve the bearing capacity such as torsion strength, compression strength, tensile strength, bending strength, strength against internal and external pressure, by 24.8%, 13.2%, 22%, 9.99% and 14.2%, respectively. The new design method of UTT pair enhances the bearing capacity of API NC38 thread, and has been applied in Changqing Drilling Company of CNPC Chuanqing Drilling Engineering Company Limited. The UTT-thread pair method is not only applicable for API series threads to improve the connection performance, but also suitable for various non-API taper connection threads to promote existing working ability such as air tightness, stress corrosion resistance, fatigue resistance et al.